A Comprehensive Analysis of Optimizing the Role of Artificial Intelligence-Based Management Information Systems in Driving Digital Transformation and Enhancing Organizational Performance in the Industry 4.0 Era - Amira S, L. Happy; ⁠Rokhadi; Hariyanti; Setyawati, Heri Tugas; Sukistanto (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to comprehensively analyze the role of Artificial Intelligence (AI)-based Management Information Systems (MIS) in supporting digital transformation and enhancing organizational performance in the Industry 4.0 era. A qualitative literature review with descriptive analysis was employed, using data sourced from 19 articles selected via Google Scholar from 2014–2024. The findings reveal that AI-based MIS significantly contribute to improving operational efficiency, supporting strategic decision-making, and fostering innovation. Case studies on PT Astra International Tbk, Bank BRI, and Tokopedia illustrate how AI implementation can optimize business processes and enhance organizational competitiveness. However, adopting this technology faces challenges such as infrastructure limitations, digital literacy gaps, and high implementation costs, particularly for SMEs. The study's implications include recommendations for organizations to prioritize infrastructure readiness and human resource development, as well as the importance of cross-sector collaboration to promote inclusive and sustainable digital transformation. This research provides theoretical contributions to the literature on AI's role in MIS and practical guidance for technology implementation across various sectors.